1994
DOI: 10.1021/j100081a015
|View full text |Cite
|
Sign up to set email alerts
|

Momentum Effects in Reaction-Diffusion Systems

Abstract: The standard formulation of reaction-diffusion equations assumes that the reacting particles undergo Brownian motion. We generalize the consequent formalism by incorporating a rudimentary model of momentum effects, based on a persistent random-walk model. This formulation is used to study some properties of the reaction A + B -C with the reactant species initially separated in space. It is shown that the change in dynamics introduces an additional short-time scaling regime in the behavior of the reaction rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 5 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…1993, 1997, Schenkel et al 1993, Lee and Cardy 1994, 1995, Vilensky et al 1994, Araujo 1995, Howard and Cardy 1995, Hoyuelos et al 1995, Krapivsky 1995, Barkema et al 1996, Koza 1996, 1997, Taitelbaum et al 1996a,b, Koza and Taitelbaum 1997, Malyutin et al 1997, Richardson and Evans 1997, Rodriguez and Wio 1997. …”
Section: $2 Methods and Resultsmentioning
confidence: 99%
“…1993, 1997, Schenkel et al 1993, Lee and Cardy 1994, 1995, Vilensky et al 1994, Araujo 1995, Howard and Cardy 1995, Hoyuelos et al 1995, Krapivsky 1995, Barkema et al 1996, Koza 1996, 1997, Taitelbaum et al 1996a,b, Koza and Taitelbaum 1997, Malyutin et al 1997, Richardson and Evans 1997, Rodriguez and Wio 1997. …”
Section: $2 Methods and Resultsmentioning
confidence: 99%
“…In many cases the predictions of the mean-field PDE agree well with simulation averages, especially at low densities of agents, but the quality of agreement degrades when inter-agent interactions have a significant attractive component [16], or when agents reproduce at random as well as moving at random. In many scenarios including modelling of vehicle movement [17], chemical reaction kinetics [18], cell motility [6] and animal movement [19], it is clear that agents do not move completely at random but exhibit short-term persistence in the direction of motion, thus giving rise to the notion of a persistent random walk (PRW) [3,19,20]. The case of non-interacting walkers has received substantial attention [3,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…products. The conditions for these front patterns are significant differences in the microscopic reaction constants and in the initial densities of the competing species.[S0031-9007(96)00897-6] 05.40.+j In a series of recent papers [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16], it has been shown that elementary reaction-diffusion systems with initially separated components have very unusual dynamical properties. For the elementary reaction A 1 B !…”
mentioning
confidence: 99%